اهم العقبات التي تواجه المخطط الاساس - فيصل جعفر, حسن (Journal of Engineering and Sustainable Development, 2018)
The process of making a master plan and carrying it out is not easy because there are a lot of obstacles in front of it, end these obstacles are different with the different of the client, the planer, and the place where the master plan is doing. And because of this, there are many obstacles that may reoccur in many cases which the research tries to indicate and to clarify the number of elements involved in the planning process as obstacles elements in both of its phases (making) and (carrying out) of this process. After clarifying these obstacles the research has limited these elements into three main titles (the planer), (the client), and (the existing conditions) to make it easy dealing with the obstacles.